THE IMPROVEMENT OF THE UNDERSTANDING OF THE STRUGGLE OF THE WARRIORS IN THE DUTCH COLONIAL PERIOD THROUGH TEAMS GAMES TOURNAMENT (TGT) LEARNING MODEL ON STUDENTS OF V GRADE SD N SURAKARTA ACADEMIC YEAR 2017/2018 - Latifah Aulia Harini; Hartono Hartono; Hadiyah Hadiyah (Universitas Sebelas Maret, 2018)
The objective of this research is to improve the understanding of the struggle of the warriors in the Dutch colonial period by applying Teams Games Tournament (TGT) learning model on students of V grade SD N Surakarta academic year 2017/2018. This research uses qualitative approach by doing classroom action research with cycle model. The data were collected by doing observation, interview, test, and documentation. The validity of the data is using content validity, triangulation technique including source triangulation and technique triangulation. The data analysis technique in this research uses interactive analysis model that includes data reduction, data display, verification. The conclusion of this research was the implementation of Teams Games Tournament (TGT) learning model, it can improve the understanding of the struggle concept of the warriors during the Dutch colonial period on students of V grade SD N Surakarta academic year 2017/2018.